Exploring variations in contracting for services among American local governments: do politics still matter? - Fernandez, Sergio; Brudney, Jeffrey L.; Ryu, Jay Eungha (2008)
During the previous two decades, researchers have conducted an array of empirical studies of local government contracting for services. Some of the more recent findings have suggested that this form of privatization has become less politically controversial and more accepted as a service delivery approach. Do politics still matter when it comes to explaining patterns in local government contracting? The findings from this study indicate that the influence of political factors, such as demand for smaller government and public employee opposition to privatization, still help to account for variations in local government contracting, as they did during the 1980s and early 1990s. Contract management capacity is an important determinant of local government contracting. - Reproduced.
Keywords: Local government - United States; Local government